The Development of Animal Models for Respiratory Syncytial Virus (RSV) Infection and Enhanced RSV Disease - Gengxin Zhang; Binbin Zhao; Jiangning Liu (Viruses)
The development of immunoprophylactic products against respiratory syncytial virus (RSV) has resulted in notable advancements, leading to an increased demand for preclinical experiments and placing greater demands on animal models. Nevertheless, the field of RSV research continues to face the challenge of a lack of ideal animal models. Despite the demonstration of efficacy in animal studies, numerous RSV vaccine candidates have been unsuccessful in clinical trials, primarily due to the lack of suitable animal models. The most commonly utilized animal models for RSV research are cotton rats, mice, lambs, and non-human primates. These animals have been extensively employed in mechanistic studies and in the development and evaluation of vaccines and therapeutics. However, each model only exemplifies some, but not all, aspects of human RSV disease. The aim of this study was to provide a comprehensive summary of the disease symptoms, viral replication, pathological damage, and enhanced RSV disease (ERD) conditions across different RSV animal models. Furthermore, the advantages and disadvantages of each model are discussed, with the intention of providing a valuable reference for related RSV research.